Challenges of the first six months COVID-19 among students : an Experience at Yogyakarta State University - Prasastiawati, Diana; Andhika, Muhammad; Sumunar, Dyah Respati Suryo (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2024)
Students and residents who live in residential areas around the campus are one of the groups vulnerable to the spread of COVID-19. This study aims to analyze the level of anticipation of vulnerability and capacity in  Yogyakarta in facing the threat of COVID-19 This research is categorized as quantitative research, with a research sample of 395 students of Yogyakarta State University. The survey method through questionnaires was used to collect primary data in the form of community vulnerability and student capacity. The research sampling technique in this research is using purposive sampling technique. The validity used is content validity and construct validity. The results of the reliability analysis of this study are 0.95 for Likert scale items (Cronbach Alpha), 0.708 for Guttman scale items (KR-20), and 0.575 for multiple choice items (Split-Half Coefficient). The results showed that in general the score of anticipating the vulnerability of Universitas Negeri Yogyakarta to the threat of COVID-19 reached 69.98% (good category). The level of capacity of students in dealing with the threat of COVID-19 is also classified as good (90.76%).